Health literacy, financial insecurity and health outcomes among people living with HIV in Australia. (11th November 2022) - Power, Jennifer; Lea, Toby; Melendez-Torres, G J; Lyons, Anthony; Norman, Thomas; Hill, Adam O; Bourne, Adam
Summary: It is well documented that lower socio-economic status is associated with poorer health outcomes, while health literacy is considered important for improving health. What is less clear, is the extent to which greater health literacy can improve health outcomes among people for whom poverty or financial insecurity are important barriers to health. The paper presents findings from an Australian survey of people living with HIV (PLHIV) ( N = 835) in which we explored the relationship between financial insecurity and health outcomes, looking at the extent to which health literacy mediates this relationship. The study drew on a comprehensive definition of health literacy, measuring participant's confidence to communicate with healthcare providers, navigate the health system and take an active stance in relation to their health. Findings showed that financial insecurity was associated with lower health literacy and poorer self-reported physical and mental health. Health literacy mediated 16.2% of the effect of financial insecurity on physical health scores and 16.6% of the effect of financial insecurity on mental health scores. This suggests that programmes which seek to build health literacy among PLHIV may improve health outcomes among PLHIV who are struggling financially. Health literacy programmes are likely to be effective if they build confidence and resourcefulness among people to engage with health information, decision-making and care.